Life cycle assessment and feasibility analysis of a combined chemical looping combustion and power-to-methane system for CO2 capture and utilization. (September 2020) - Bareschino, P.; Mancusi, E.; Urciuolo, M.; Paulillo, A.; Chirone, R.; Pepe, F.
Abstract: The ability to store effectively excess of electrical energy from peaks of production is key to the development of renewable energies. Power-To-Gas, and specifically Power-To-Methane represents one of the most promising option. This works presents an innovative process layout that integrates Chemical Looping Combustion of solid fuels and a Power-to-Methane system. The core of the proposed layout is a multiple interconnected fluidized bed system (MFB) equipped with a two-stage fuel reactor (t-FR). Performances of the system were evaluated by considering a coal as fuel and CuO supported on zirconia as oxygen carrier. A kinetic scheme comprising both heterogeneous and homogeneous reactions occurring in the MFB was considered. The methanation unit was modelled developing a thermodynamic calculation method based on minimization of the free Gibbs energy. The performance of the system was evaluated by considering that the CO/CO2 stream coming from the t-FR reacts over Ni supported on alumina catalyst with a pure H2 stream generated by an array of electrolysis cells. The number of cells to be stacked in the array was evaluated by considering that a constant H2 production able to convert the whole CO/CO2 stream produced by the CLC process should be attained. The environmental performance of the proposed process was quantified using the Life Cycle Assessment (LCA) methodology. The analysis shows i) that the majority originate from the production and disposal of the oxygen carrier used in the t-FR, and ii) that reusing part of the oxygen produced by the electrolysis cells improves significantly the environmental performance of the proposed process. Highlights: Feasibility of a system coupling CLC and CO2 methanation was numerically tested. Near-zero CO2 emissions and a 13% electric energy storage efficiency was assessed. LCA identified OC production and disposal as the main source of environmental impacts. Strategies to improve environmental performances were consequently presented and assessed.